Education on the Making of Ginger Powder Herbal Drink in the Benangka Community in Banangkah Village (Benangkah), Burneh District, Bangkalan, East Java - Riza Aulia Widyaningsih; Jennis Pretty Aprilia; Siti Nurhalimah; Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia is the largest producer of spices, one of which is ginger. Ginger is a plant that is easily grown in all types of soil, so it is easy to obtain, apart from cooking spices, ginger can also be used as an instant drink which is beneficial for the health of the body. Instant ginger powder is made from 100% ginger which is processed using household appliances so that everyone can make instant ginger powder drink easily and practically. The purpose of the community service in the village of Bangkalan, Bangkalan Regency, is to socialize the manufacture of good and correct instant ginger powder, so that it can produce really good powder, while the benefits are that many people still do not understand about instant ginger powder and its contents and benefits. The results of the dedication That from the ginger plant to instant powder and even the dregs can be used for some minor ailments that they don't know about and how to process ginger into instant ginger powder.